Piecing together human adult comparative pharmacokinetic trials and rodent studies: What happens to drug clearance in obesity? - Dion Brocks; Hamdah Al Nebaihi; Shamima Parvin; Amel Hamza (Frontiers Media S.A., 2022)
In many comparative trials examining the effects of adult obesity on pharmacokinetics of drugs, conclusions were made based on values that were either not adjusted to total body weight or adjusted to non-obese body mass (e.g., ideal or lean body weight). In many cases these values were higher in the obese subjects. We have reviewed the data from comparative human trials, and it is apparent that in examining clearance normalization to total body weight (as typically done in studies involving pediatric obese patients), the clearances are often reduced in the obese. We have also reviewed the results of experimental obese versus non-obese rodent models. Those studies have mostly found that the systemic exposures to the same dose per body weight are increased, with obesity-related decreases in clearance. Furthermore, the expression of a number of important drug metabolizing enzymes are reduced in the experimental obese state. There is also evidence that obesity causes increases in the measured mass of eliminating organs such as liver and kidney. Human clearance normalized to total body weight appears to better reflect the underlying changes reported in the expression of protein and functional activity of drug clearance mechanisms.